Contemporary techniques of da Vinci SP radical prostatectomy: multicentric collaboration and expert opinion - Moschovas,Marcio Covas (2022)
ABSTRACT Background The da Vinci SP robot consists of an innovative single port trocar that houses a flexible camera and three biarticulated arms, which minimizes the number of incisions to assess the surgical site, allowing a less invasive procedure. However, due to its recent release in the market, the current literature reporting SP-RARP is still restricted to a few centers. In this scenario, after performing a literature search with all available techniques of SP-RARP, our objective is to report a multicentric opinion of referral centers on different techniques to approach SP-RARP. Results The SP literature is provided by only a few centers due to the limited number of this new console in the market. Five different approaches are available: transperitoneal, extraperitoneal, Retzius-Sparing, transperineal and transvesical. None of the current studies describe long-term functional or oncological outcomes. However, all approaches had satisfactory operative performance with minimum complication rates. Conclusions Several techniques of SP-RARP have been reported in the literature. We performed a multicentric collaboration describing and illustrating the most challenging steps of this surgery. We believe that the details provided in this article are useful teaching material for new centers willing to adopt the SP technology.